2018
DOI: 10.1002/jcp.26510
|View full text |Cite
|
Sign up to set email alerts
|

The importance of miRNAs and epigenetics in acute lymphoblastic leukemia prognosis

Abstract: Acute lymphoblastic leukemia (ALL), one of the most common malignant human disorders, originates in different important genetic lesions in T-cell or B-cell progenitors. ALL is a malignant lymphoid progenitor with peak prevalence in children (2-5 years). The rate of survival when one is suffering from ALL depends on various agents including the age of the patient, responses to anti-leukemic therapy, and cell biology. miRNAs and epigenetics are important regulatory factors in the expression of genes. miRNAs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 130 publications
0
14
0
Order By: Relevance
“…MiRNAs are small non-coding RNAs of about 19–24 nucleotides, which inhibit the translation of proteins by binding to 3′-UTR of the target mRNA. Some studies have also found that miRNAs can interact directly with proteins to regulate gene expression [1] or influence the epigenetic mechanisms [2]. As a non-invasive blood biomarker, miRNAs are relatively stable and easy to detect.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are small non-coding RNAs of about 19–24 nucleotides, which inhibit the translation of proteins by binding to 3′-UTR of the target mRNA. Some studies have also found that miRNAs can interact directly with proteins to regulate gene expression [1] or influence the epigenetic mechanisms [2]. As a non-invasive blood biomarker, miRNAs are relatively stable and easy to detect.…”
Section: Introductionmentioning
confidence: 99%
“…In their roles in cancer, miRNAs are found to act as both oncogenes, by stimulating tumor growth and metastasis, and tumor suppressor genes, by inhibiting tumor cell proliferation and dissemination, as well as in inducing apoptosis [ 36 , 37 , 38 ]. Recent studies have demonstrated that miRNAs directly interact with proteins, thereby either regulating gene expression or influencing epigenetic mechanisms [ 39 , 40 , 41 ].…”
Section: Mirnas and Nutritionmentioning
confidence: 99%
“…Small noncoding RNAs with a length of 19–24 nucleotides are known as miRNAs, which suppresses the protein translation via binding to 3′‐UTR of the mRNAs 111 . It has been shown that the direct interaction of miRNAs with proteins has regulated gene expression and affected the epigenetic mechanisms as well 112,113 . miRNAs are noninvasive blood biomarkers that are quite stable and easily separable.…”
Section: Mirnas Detectionmentioning
confidence: 99%